Polymer additive as well as preparation method and application thereof
By optimizing the crystal structure in the polymer additives of aluminum diethylphosphinate and aluminum ethylbutylphosphinate, the corrosion problem of aluminum diethylphosphinate during processing is solved, and better resistance is achieved Thermal stability and reduce corrosion to metal equipment.
Patent Information
- Application Number
- CN202411875706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Aluminum diethylphosphinate has severe corrosion on the screw during the process of flame retardant modified engineering plastics and special engineering plastics. The prior art improves by combining other components, but there are still corrosion problems.
Using polymer additives of aluminum diethylphosphinate and aluminum ethylbutylphosphinate within a specific double-enthalpy ratio and thermal analysis temperature range, the crystal structure is optimized through differential scanning calorimetry DSC test to reduce the processing process decomposition and corrosion in.
It significantly reduces the corrosion of polymer additives to metal production equipment, and improves its heat resistance and processing performance.
Smart Images

Figure CN119307006A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flame retardants, and more specifically, relates to a polymer additive and a preparation method and application thereof. Background Art
[0002] Aluminum diethylphosphinate is a halogen-free, green and environmentally friendly flame retardant. It appears as a white powder. It is insoluble in water and most organic solvents, but easily soluble in strong acid and strong alkali solutions. It has the characteristics of high efficiency flame retardancy, high thermal stability, low smoke, small particle size, low specific gravity, good dispersibility and compatibility. As an efficient, green and environmentally friendly halogen-free flame retardant, aluminum diethylphosphinate is widely used in flame retardant products such as thermoplastics (such as PPA, PA66, PBT), fibers and textiles.
[0003] The compound system of aluminum diethylphosphinate is widely used in the field of halogen-free flame-retardant glass fiber reinforced engineering plastics, such as the aluminum diethylphosphinate compounded with melamine polyphosphate (MPP) system, the aluminum diethylphosphinate and melamine cyanuric acid (MCA) system, and the aluminum diethylphosphinate and aluminum phosphite system. These systems have the advantages of high flame retardant efficiency, high temperature resistance, and low loss of resin matrix performance, and are widely used.
[0004] Although conventional aluminum diethylphosphinate has a high heat resistance temperature, and most of the quality specifications of products on the market require that the 1wt% thermal weight loss temperature is greater than 350°C (nitrogen atmosphere, 20°C / min), its corrosion to the screw is still relatively serious during the process of flame retardant modified engineering plastics (such as PBT, PA, etc.), especially special engineering plastics (such as high-temperature nylon, etc.), and needs to be improved in conjunction with some additives.
[0005] At present, relevant literature has studied the thermal degradation and flame retardant mechanism of aluminum diethylphosphinate. It is found that during the decomposition process of aluminum diethylphosphinate, diethylphosphinate and other acidic substances will be decomposed and volatilized into the gas phase, fully cracked into phosphorus atoms, and then formed into a phosphorus-containing free radical quencher to play a gas phase flame retardant role. Patent CN107189098A discloses an additive for polymers. The use of aluminum diethylphosphinate and aluminum phosphite and / or alkyl aluminum phosphite for compounding can greatly reduce the corrosion of the screw and have less impact on the color of the polymer body. Patent CN110407869A discloses a monotrifluoropropyl phosphinate aluminum flame retardant. The use of monotrifluoropropyl phosphinate aluminum and diethylphosphinate aluminum compound can reduce the corrosion of diethylphosphinate to the screw during the extrusion modification process.
[0006] However, the above solution improves the corrosiveness of aluminum diethylphosphinate by compounding other components with aluminum diethylphosphinate. However, aluminum diethylphosphinate still suffers from severe corrosion during screw extrusion. Therefore, how to provide aluminum diethylphosphinate with lower corrosivity has become a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the above-mentioned existing technical problems, the object of the present invention is to provide a polymer additive, which has good heat resistance and stability and can significantly reduce the corrosion of metal processing parts of metal production equipment during the flame retardant modification process.
[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions: A polymer additive, comprising aluminum diethylphosphinate having a structural formula shown in the following formula (I) and aluminum ethylbutylphosphinate having a structural formula shown in the following formula (II);
[0009] The polymer additive satisfies the double enthalpy ratio ΔH defined by the following formula (1): 0.92≤ΔH≤1.06; and satisfies 130°C≤T1≤155°C, 165°C≤T2≤185°C; Formula (1) ΔH = H2 / H1; The polymer additive is tested by differential scanning calorimetry (DSC), and the testing method is as follows: in a nitrogen atmosphere, the polymer additive is heated from room temperature to a maximum temperature of 300°C at a heating rate of 20°C / min, and then cooled to room temperature at a rate of 20°C / min after staying at this temperature for 3 minutes, to obtain a cooling curve of the polymer additive, and the polymer additive is heated to a maximum temperature of 300°C at a heating rate of 20°C / min again after staying at room temperature for 3 minutes, to obtain a second heating curve of the polymer additive; H1 is the peak area formed by the starting temperature and the ending temperature of the exothermic peak on the cooling curve, and T1 is the peak temperature of the exothermic peak on the cooling curve; H2 is the peak area formed by the starting temperature and the ending temperature of the endothermic peak on the second temperature rising curve, and T2 is the peak temperature of the endothermic peak on the second temperature rising curve.
[0010] Differential Scanning Calorimetry (DSC) is used to characterize the melting and crystallization process of polymers. It can reflect the relationship between polymer structure and crystallization. The change of polymer structure directly determines the melting or crystallization behavior of DSC during heating or cooling. The physical meaning of the actual reaction of the double enthalpy ratio ΔH is the destruction of the polymer crystal structure, and the relationship between the difficulty of crystallization and the polymer structure. Crystallization behavior is closely related to the melting behavior and structural characteristics of the crystal. There are great differences in the structure of polymers. The crystallization behavior of polymer arrangement and the destruction behavior of the crystal structure have great changes, which is reflected in the melting enthalpy and crystallization enthalpy changes of DSC (that is, the double enthalpy ratio). There is a certain volatility, and this fluctuation of the double enthalpy ratio reflects the structural characteristics of the polymer and the resulting changes in the macroscopic thermal stability of the polymer.
[0011] Through research, the inventors found that under the premise of a specific double enthalpy ratio, T1 and T2, the polymer additive has a specific structure. This structure makes it more difficult to destroy the crystal structure and morphology of the polymer additive during the heating process, thereby having better heat resistance and stability, reducing the decomposition of the polymer additive during the processing process, and significantly reducing the corrosion of metal processing parts (such as screws) of metal production equipment.
[0012] Specifically, in some embodiments, the peak areas H1, H2 and peak positions T1, T2 can be obtained by peak marking and integral calculation of peak areas using existing methods in the art, such as peak marking and integral calculation of peak areas using software provided in the DSC device. Specifically, in some embodiments, when using differential scanning calorimetry DSC for testing, the weight of the test sample of the polymer additive can be 10±0.5 mg.
[0013] Specifically, in some embodiments, the peak areas H1, H2 and the peak positions T1, T2 can be integrated or marked multiple times and then averaged and tested, such as once, twice, three times, four times, five times, etc. More specifically, from the perspective of saving operations and maintaining data reproducibility and reliability, the peak areas H1, H2 and the peak positions T1, T2 can be tested 2-4 times and averaged and obtained.
[0014] In some embodiments, the polymer additive comprises, by weight percentage, 97.01% to 98.99% aluminum diethylphosphinate and 1.01% to 2.99% aluminum ethylbutylphosphinate. More specifically, the content of aluminum diethylphosphinate may be 97.30%, 97.50%, 97.70%, 97.90%, 98.10%, 98.30%, 98.50%, 98.70%, 98.90%, etc., or an interval range formed by any of the above values, such as 97.01 to 97.70%, 97.30 to 97.90%, 97.01 to 98.30%, 98.10 to 98.50%, 98.90 to 98.99%, 98.50 to 98.90%, etc., and the present invention is not limited thereto. More specifically, the content of ethylbutyl aluminum phosphinate can be 1.20%, 1.40%, 1.60%, 1.80%, 2.00%, 2.20%, 2.40%, 2.60%, 2.80%, 2.90%, etc., or an interval range formed by any of the above values, such as 1.01-2.50%, 1.01-2.20%, 1.10-2.20%, 1.40-2.20%, 1.80-2.60%, etc., but the present invention is not limited thereto.
[0015] In some embodiments, the polymer additive satisfies a double enthalpy ratio ΔH: 0.93≤ΔH≤1.05; the polymer additive satisfies 132°C≤T1≤153°C, 170°C≤T2≤183°C.
[0016] More specifically, the dual enthalpy ratio ΔH of the present invention can be 0.93, 0.94, 0.96, 0.98, 1.00, 1.02, 1.04, etc., or an interval range formed by any of the above values, such as 0.95-1.02, 0.96-1.00, etc., but the present invention is not limited thereto.
[0017] The T1 described in the present invention may be 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C, 150°C, 152°C, 154°C, 155°C, etc., or an interval range formed by any of the above values, such as 134°C to 142°C, 140°C to 154°C, etc., but the present invention is not limited thereto.
[0018] The T2 described in the present invention may be 165°C, 167°C, 169°C, 171°C, 173°C, 175°C, 177°C, 179°C, 181°C, 183°C, 185°C, etc., or an interval range formed by any of the above values, such as 167°C to 175°C, 171°C to 177°C, etc., but the present invention is not limited thereto.
[0019] Further preferably, the polymer additive satisfies the double enthalpy ratio ΔH: 0.92≤ΔH≤0.93, and satisfies 146℃≤T1≤148℃, 178℃≤T2≤180℃; within this preferred range, the polymer additive has better heat resistance and stability, and causes less corrosion to the screw during the extrusion modification process.
[0020] In some embodiments, the water content of the polymer additive is 0.05% to 0.40 wt %.
[0021] In some embodiments, the bulk density of the polymer additive is 150 to 800 g / L; preferably 350 to 750 g / L.
[0022] In some embodiments, the water solubility of the polymer additive is 0.01 to 5 g / L.
[0023] Further, in some embodiments, the present invention provides a method for preparing a polymer additive, comprising the following steps: a) a water-soluble salt or acid of hypophosphorous acid and an initiator are introduced into a jet loop reaction system to react with an olefin, and 2.00 to 2.05 molecules of olefin are added relative to the P of each water-soluble salt or acid of hypophosphorous acid itself to obtain an intermediate aqueous solution containing diethylphosphinate; b) The intermediate aqueous solution undergoes double decomposition reaction with a water-soluble aluminum salt to obtain a polymer additive.
[0024] In the above embodiment, in step a), the pressure of olefin in the jet loop reaction system is 0.3-3.0 MPa.
[0025] In the above embodiment, in step a), the reaction temperature in the jet loop reaction system is 70-150°C.
[0026] Further preferably, in some embodiments, the pressure of olefins in the jet loop reaction system is 1.2-1.6 MPa; and the reaction temperature in the jet loop reaction system is 100-110°C.
[0027] In the above embodiment, in step b), the mass concentration of diethylphosphinate in the intermediate aqueous solution is 20-25%.
[0028] In the above embodiment, the mass concentration of the water-soluble aluminum salt in the water-soluble aluminum salt solution is 20-25%.
[0029] In the above embodiment, in step b), the pH of the metathesis reaction is 3.0-3.1.
[0030] In the above embodiment, in step b), the temperature of the metathesis reaction is 40-45°C.
[0031] In the above embodiment, in step b), the molar ratio of diethylphosphinate to aluminum ions in the water-soluble aluminum salt is 3:1 to 1.01.
[0032] In the above embodiment, the jet loop reaction system comprises at least one set of jet loop reaction device and 0 to 3 maturation reactors; or the jet loop reaction system may also be a set of intermittent jet loop reaction device without a maturation reactor. When the jet loop reaction system comprises multiple sets of continuous jet loop reaction devices, the multiple jet loop reaction devices and the maturation reactor are connected in parallel or in series.
[0033] In the above embodiment, the jet loop reaction device can be a reactor with stirring or a jet loop reactor without stirring; the maturation reactor can be a high-pressure reactor, a jet loop reactor, a plate tower, a bubble tower, a falling film reaction tower, etc.
[0034] In the above embodiment, when the intermediate aqueous solution is mixed with the water-soluble aluminum salt, the intermediate aqueous solution can be dripped into the water-soluble aluminum salt; or the intermediate aqueous solution and the water-soluble aluminum salt can be dripped into the reactor at the same time.
[0035] Further, in some embodiments, the present invention provides another method for preparing a polymer additive, comprising the following steps: a) under nitrogen protection, a water-soluble salt or acid of hypophosphorous acid reacts with an olefin in the presence of an initiator at 90-100° C., keeping the temperature, and adding 2.00 to 2.05 molecules of olefin relative to each P on the water-soluble salt or acid of hypophosphorous acid itself to obtain an intermediate aqueous solution containing diethylphosphinate; b) Under stirring, the intermediate aqueous solution and the water-soluble aluminum salt are mixed and reacted at ≤15°C, and then the temperature is raised to 70-95°C and kept warm to obtain a polymer additive.
[0036] In the above embodiment, in step a), the heat preservation is carried out in two steps, the first heat preservation time is 3.5 to 4.5 hours, and the initiator is continuously added during the heat preservation process; then the heat preservation is continued for 0.5 to 1.5 hours.
[0037] In the above embodiment, in the step b), the mixing reaction is carried out at 0-10°C.
[0038] In the above embodiment, in the step b), the pH of the reaction is 3.0 to 7.0.
[0039] In the above embodiment, in the step b), the water-soluble aluminum salt is added dropwise to the intermediate aqueous solution under stirring for mixing and reaction, and the adding time is 1.5 to 2.5 hours.
[0040] In the above embodiment, in the step b), the heating rate is 2-15° C. / h.
[0041] In the above embodiment, in step b), the insulation time is 5 to 30 minutes.
[0042] In the above embodiment, in step b), the molar ratio of diethylphosphinate to aluminum ions in the water-soluble aluminum salt is 3:1 to 1.01.
[0043] Further, in some embodiments, the present invention provides another method for preparing a polymer additive, comprising the following steps: a) under nitrogen protection, an aqueous solution of hypophosphorous acid reacts with an olefin in the presence of an initiator at 90-100° C., keeping the temperature, and adding 2.00 to 2.05 molecules of olefin relative to the P of each hypophosphorous acid acid itself to obtain an intermediate aqueous solution containing diethylphosphinic acid; b) preparing an aluminum hydroxide gel solution; c) dropping the intermediate aqueous solution into the aluminum hydroxide gel solution for reaction, raising the temperature to 90-120° C., keeping the temperature for 0.1-5 hours, and post-treating to obtain the polymer additive.
[0044] In the above embodiment, in step a), the heat preservation is carried out in two steps, the first heat preservation time is 2.5 to 3.5 hours, and the initiator is continuously added during the heat preservation process; then the heat preservation is continued for 1.5 to 2.5 hours.
[0045] In the above embodiment, during the heat preservation process of step a), part of the reaction materials in the reactor are introduced into the venturi ejector and fully mixed with the ethylene introduced into the venturi ejector, and then enter the reactor after external circulation.
[0046] In the above embodiment, in step b), an aqueous sodium hydroxide solution is dripped into an aqueous aluminum sulfate solution to obtain an aluminum hydroxide gel solution.
[0047] In the above embodiment, in the step b), the temperature during the dropping is 10-20°C.
[0048] In the above embodiment, in the step c), the heating rate is 2 to 25° C. / h.
[0049] In the above embodiment, in step c), the molar ratio of diethylphosphinic acid to aluminum ions in the aluminum hydroxide gel solution is 3:1 to 1.01.
[0050] In some embodiments, the initiator is selected from one or more of organic peroxides, inorganic peroxides, and azo compounds. More specifically, the inorganic peroxide may be one or more of sodium persulfate, ammonium persulfate, or potassium persulfate. The organic peroxide may be one or more of benzoic acid peroxide, lauric acid peroxide, di-tert-butyl peroxide, peroxycarbonate, peroxyacetic acid, tert-butyl peroxyisobutyrate, tert-butyl peroxypivalate, or tri-amyl peroxide; the azo compound may be one or more of azobisisobutyronitrile or azobisisoheptylonitrile.
[0051] In some embodiments, the olefin may be at least one of ethylene, propylene, 1-butene, 2-butene, 1-pentene, 1-hexene, or 1-octene.
[0052] In some embodiments, the water-soluble salt of hypophosphorous acid may be potassium hypophosphite or sodium hypophosphite.
[0053] In some embodiments, the water-soluble aluminum salt may be an oxide, hydroxide, peroxide, sulfate, bisulfate, hydrated sulfate, persulfate, phosphate, and / or phosphite of aluminum.
[0054] Furthermore, the present invention claims to protect the use of the polymer additive in reducing corrosion of metal production equipment, especially in reducing corrosion of metal parts of metal production equipment, such as screws.
[0055] Furthermore, the invention claims the use of the polymer additive as a reactive or non-reactive flame retardant for polymers, as a flame retardant for varnishes and foamed coatings, as a flame retardant for wood and other cellulose-containing products, for the preparation of flame-retardant polymer molding materials, for the preparation of flame-retardant polymer moldings or for imparting flame retardancy to polyesters and pure and blended cellulose fabrics by impregnation.
[0056] Further, the polymer additive is used together with a synergist; the synergist is melamine phosphate, di(melamine) phosphate, penta(melamine) triphosphate, tri(melamine) diphosphate, tetra(melamine) triphosphate, hexa(melamine) pentaphosphate, melamine diphosphate, melamine tetraphosphate, melamine pyrophosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate and / or melon polyphosphate; a melamine condensation product such as melam, melem and / or melon; an oligoester of tri(hydroxyethyl) isocyanurate / salt and aromatic polycarboxylic acid, benzoguanamine, tri(hydroxyethyl) isocyanurate, ) isocyanurate / salt, allantoin, glycoluril, melamine, melamine cyanurate, urea cyanurate, dicyandiamide and / or guanidine; a nitrogen-containing phosphate of the formula (NH4)yH3-yPO4 or (NH4PO3)z, wherein y is 1 to 3 and z is 1 to 10000; aluminum phosphite, aluminum pyrophosphite; zinc borate, zinc carbonate, zinc stannate, basic zinc stannate, zinc phosphate, zinc oxide, zinc hydroxide, tin oxide hydrate, basic zinc silicate, magnesium hydroxide, hydrotalcite, magnesium carbonate; a salt of ethylphosphonic acid, a salt of butylphosphonic acid, a salt of n-butylphosphonic acid, a salt of sec-butylphosphonic acid and / or a salt of hexylphosphonic acid.
[0057] Further, the polymer additive is used together with other additives, wherein the other additives are at least one of antioxidants, UV stabilizers, gamma ray stabilizers, hydrolysis stabilizers, antistatic agents, emulsifiers, nucleating agents, softeners, processing aids, impact modifiers, dyes or pigments.
[0058] Furthermore, 0.0001 to 99.7999 wt % of the polymer additive, 0.1 to 40 wt % of the synergist and 0.1 to 40 wt % of other additives are used.
[0059] Further, the present invention claims a flame retardant thermoplastic or thermosetting polymer composite material comprising: 0.5 to 45 wt % of the polymer additive, 0.5 to 95 wt % of a thermoplastic or thermosetting polymer or a mixture thereof, 0 to 55 wt % of a synergist and 0 to 55 wt % of a filler or reinforcing material.
[0060] In some embodiments, the thermoplastic or thermosetting polymer or mixtures thereof is selected from polyesters, polyamides, thermoplastic elastomers, thermoplastic polyurethanes, thermoplastic polyester elastomers, styrenic polymers, polyketones, polyolefins, polyacrylates and / or polymer blends or other blends comprising polyamides or polyesters.
[0061] In some embodiments, the flame retardant thermoplastic or thermosetting polymer composite material may be a flame retardant thermoplastic or thermosetting polymer molding material, a polymer formed body, a polymer film, a polymer filament, or a polymer fiber.
[0062] In some embodiments, the polyolefins may be polymers of monoolefins and dienes, such as polypropylene, polyisobutylene, poly-1-butene, poly-4-methyl-1-pentene, polyisoprene or polybutadiene, and polymers of cyclic olefins, such as cyclopentene or norbornene; furthermore polyethylenes (which may optionally be crosslinked), such as high-density polyethylene (HDPE), high-density and high-molar-mass polyethylene (HDPE-HMW), high-density and ultra-high-molar-mass polyethylene (HDPE-UHMW), medium-density polyethylene (MDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), branched low-density polyethylene (VLDPE) and mixtures thereof.
[0063] The polyolefin may also be a copolymer of a monoolefin and a diene with each other or with other vinyl monomers, for example, ethylene propylene copolymer, linear low density polyethylene (LLDPE) and its mixture with low density polyethylene (LDPE), propylene-1-butene copolymer, propylene-isobutylene copolymer, ethylene-1-butene copolymer, ethylene-hexene copolymer, ethylene-methylpentene copolymer, ethylene-heptene copolymer, ethylene-octene copolymer, propylene-butadiene copolymer, isobutylene-isoprene copolymer, ethylene-alkyl acrylate copolymer, ethylene-alkyl methylpropionate copolymer, ethylene-vinyl acetate copolymer. Polymers and their copolymers with carbon monoxide, or ethylene-acrylic acid copolymers and their salts (ionomers), and terpolymers of ethylene with propylene and a diene, such as hexadiene, dicyclopentadiene or ethylidene norbornene; furthermore mixtures of such copolymers with one another, for example polypropylene / ethylene-propylene copolymers, LDPE / ethylene-vinyl acetate copolymers, LDPE / ethylene-acrylic acid copolymers, LLDPE / ethylene-vinyl acetate copolymers, LLDPE / ethylene-acrylic acid copolymers and alternating or statistically constructed polyalkylene / carbon monoxide copolymers and mixtures thereof with other polymers, such as polyamides.
[0064] In some embodiments, the styrenic polymer can be a copolymer of styrene or α-methylstyrene with a diene or acrylic derivative, such as styrene-butadiene, styrene-acrylonitrile, styrene-alkyl methacrylate, styrene-butadiene-alkyl acrylate and styrene-butadiene-alkyl methacrylate, styrene-maleic anhydride, styrene-acrylonitrile-methyl acrylate; a high impact strength mixture from a styrene copolymer and another polymer such as a polyacrylate, a diene polymer or an ethylene-propylene-diene terpolymer; and block copolymers of styrene, such as styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene / butylene-styrene or styrene-ethylene / propylene-styrene. In some embodiments, the styrenic polymer can be a graft copolymer of styrene or α-methylstyrene, such as styrene grafted on polybutadiene, styrene grafted on polybutadiene-styrene copolymer or polybutadiene-acrylonitrile copolymer, styrene and acrylonitrile (or methacrylonitrile) grafted on polybutadiene; styrene, acrylonitrile and methyl methacrylate grafted on polybutadiene; styrene and maleic anhydride grafted on polybutadiene; styrene, acrylonitrile and maleic anhydride or maleimide grafted on polybutadiene; styrene and maleimide grafted on polybutadiene, styrene and alkyl acrylate or alkyl methacrylate grafted on polybutadiene, styrene and acrylonitrile grafted on ethylene-propylene-diene terpolymer, styrene and acrylonitrile grafted on polyalkyl acrylate or polyalkyl methacrylate, styrene and acrylonitrile grafted on acrylate-butadiene copolymer, and mixtures thereof, such as those referred to as ABS polymers, MBS polymers, ASA polymers or AES polymers, etc.
[0065] In some embodiments, the polyamide can be a polyamide and copolyamide derived from diamines and dicarboxylic acids and / or derived from aminocarboxylic acids or the corresponding lactams, such as PA6, PA66, PA46, etc.; an aromatic polyamide from meta-xylene, a diamine and adipic acid; a polyamide prepared from hexamethylenediamine and isophthalic acid and / or terephthalic acid and optionally an elastomer as a modifier (polyhexamethylene isophthalamide, polyhexamethylene terephthalamide), such as poly-2,4,4-trimethylhexamethylene terephthalamide or poly-m-phenylene isophthalamide; or a block copolymer of a polyamide with a polyolefin, an olefin copolymer, an ionomer or a chemically bonded or grafted elastomer; or a block copolymer with a polyether, such as polyethylene glycol, polypropylene glycol or polybutylene glycol.
[0066] In some embodiments, the polyester can be a polyester derived from a dicarboxylic acid and a diol and / or derived from a hydroxycarboxylic acid or the corresponding lactone, such as polyethylene terephthalate, polybutylene terephthalate, poly-1,4-dihydroxymethylcyclohexane terephthalate, polyhydroxybenzoates, and block polyetheresters derived from polyethers having hydroxyl end groups; and polyesters modified with polycarbonate or MBS.
[0067] In some embodiments, the filler or reinforcing material can be an oxygen-containing compound of silicon, a magnesium compound, such as a metal carbonate of a metal of the second main group of the periodic table, magnesium oxide, magnesium hydroxide, hydrotalcite, dihydrotalcite, magnesium carbonate or magnesium calcium carbonate; a calcium compound such as calcium hydroxide, calcium oxide, hydrocalumite, an aluminum compound such as aluminum oxide, aluminum hydroxide, boehmite, gibbsite or aluminum phosphate, red phosphorus, a zinc compound, or glass fiber.
[0068] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a polymer additive, whose double enthalpy ratio ΔH and T1, T2 are within a specific range, so that the polymer additive has a specific crystal structure and morphology, and thus has better heat resistance stability, making the polymer additive more difficult to decompose during processing, thereby reducing its corrosion to metal processing parts of metal production equipment. DETAILED DESCRIPTION
[0069] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0070] The raw materials of the embodiments and comparative examples are described as follows: Sodium hypophosphite monohydrate, commercially available.
[0071] Sodium persulfate, commercially available.
[0072] Aluminum sulfate 18hydrate, commercially available.
[0073] Fiberglass, ECS10-03-568H, Jushi Co., Ltd.
[0074] Melamine polyphosphate, BUDIT3141, BASF.
[0075] Base resin 1: PA66, EPR24, Henan Shenma.
[0076] Base resin 2: PA6, M2000, Guangdong Xinhui Meida.
[0077] Base resin 3: PBT, GX121, Yizheng Chemical.
[0078] Unless otherwise specified, the components used in the parallel embodiments and comparative examples are all the same commercially available products.
[0079] Example 1 (1) Preparation of an aqueous intermediate solution containing sodium diethylphosphinate. The specific operation is as follows: 1) A sodium hypophosphite monohydrate aqueous solution (the mass concentration of sodium hypophosphite is 35%), an initiator sodium persulfate aqueous solution (the mass concentration of sodium persulfate is 20%), and ethylene are introduced into a first jet loop reactor (1000 L), and the ethylene pressure of the first jet loop reactor is controlled to be 1.6 MPa and the temperature is controlled to be 105° C. for continuous reaction. After the materials in the first jet loop reactor are continuously reacted, they are introduced into a second jet loop reactor (2000 L) for continuous reaction. At the same time, initiator and ethylene are added to the second jet loop reactor, and the ethylene pressure of the second jet loop reactor is controlled to be 1.2 MPa and the temperature is controlled to be 100° C.; the discharge space velocity ratio of the jet loop reactor system is selected to be 0.2 / h; 2) After the reaction, the materials in the second jet loop reactor enter two parallel aging kettles (5000L) respectively. The aging kettles are supplemented with initiator and ethylene at the same time. The ethylene pressure of the two aging kettles is 1.0MPa and the temperature is 95℃; 3) The feed rate of sodium hypophosphite monohydrate aqueous solution is 300 kg / h, the feed rate of total sodium persulfate aqueous solution is 23 kg / h, the sodium persulfate aqueous solution is distributed in the mass ratio of the first jet loop reactor: the second jet loop reactor: the two aging kettles = 3:1:0.3, the speed and pressure of ethylene entering the reactor are maintained through the regulating valve, and the pressure and temperature of each reactor are maintained. After the aging kettle is aged, the ethylene pressure no longer decreases, and an intermediate aqueous solution containing sodium diethylphosphinate is obtained.
[0080] (2) Preparation of polymer additives The aqueous solution of the intermediate containing sodium diethylphosphinate prepared in the above step (1) is diluted with water to a mass concentration of 20%, 500 kg of which is heated to 40° C. and dripped into 308.4 kg of an aqueous solution of aluminum sulfate 18hydrate with a mass concentration of 25% and a pH of 3.0-3.1 to carry out a double decomposition reaction (the pH during the reaction is 3.0-3.1, and the reaction temperature is maintained at 40° C.). The dripping time is 120 min. After the dripping is completed, the solution is cooled and filtered in sequence. The filter cake is washed three times with water 3 times the weight of the filter cake, and then dried at 120° C. to constant weight to obtain a polymer additive.
[0081] Example 2 (1) Preparation of an aqueous intermediate solution containing sodium diethylphosphinate. The specific operation is as follows: 1) 479.6 kg of a 35% sodium hypophosphite monohydrate aqueous solution is introduced into a jet loop reactor (volume 1000 L) at one time; ethylene is introduced into the jet loop reactor, and the pressure of the added ethylene is controlled to be 1.2 MPa, and the temperature is 105° C. for continuous reaction; a 20% sodium persulfate aqueous solution as an initiator is continuously added into the jet loop reactor at a feeding acceleration of 4.5 kg / h. After about 4 hours, the ethylene pressure stops decreasing, and the reaction is terminated to obtain an intermediate aqueous solution containing sodium diethylphosphinate.
[0082] (2) Preparation of polymer additives The intermediate aqueous solution containing sodium diethylphosphinate is diluted with water to a mass concentration of 24%, 500 kg is taken, heated to 45°C, and dropped into 462.5 kg of 20% aluminum sulfate 18hydrate aqueous solution with a pH of 3.0-3.1 for double decomposition reaction (the pH during the reaction is 3.0-3.1, and the reaction temperature is maintained at 45°C). The dropping time is 180 minutes. After the dropping is completed, it is cooled and filtered in sequence. The filter cake is washed 3 times with water 3 times the weight of the filter cake, and then dried at 120°C to constant weight to obtain a polymer additive.
[0083] Example 3 (1) 318 g of solid sodium hypophosphite monohydrate, 500 g of water and 3 g of sodium persulfate aqueous solution (concentration of 20 wt%) were placed in an autoclave, the air in the autoclave was replaced by nitrogen, ethylene was passed through a pressure reducer to a constant pressure of 1.6 MPa, the autoclave was heated to 95° C. and kept warm for 4 h, the sodium persulfate aqueous solution was continuously added during the 4 h of keeping warm, and then kept warm at 95° C. for 1 h, cooled, and vented to obtain an intermediate aqueous solution containing diethylphosphinate; (2) The intermediate aqueous solution containing all diethylphosphinate was diluted with water to a mass concentration of 20%, cooled to 3°C, and a 3°C aluminum sulfate aqueous solution prepared by 333 g of aluminum sulfate 18hydrate and 1332 g of water was added dropwise under stirring within 2 h. After the addition was completed, the solution was heated to 90°C at a heating rate of 10°C / h, kept warm for 10 minutes, filtered, and the filter cake was washed three times with water in an amount three times the weight of the filter cake, and dried to constant weight to obtain a polymer additive.
[0084] Example 4 The difference between Example 4 and Example 3 is that in step (2), the intermediate aqueous solution is diluted to 20%, cooled to 3°C, and a 3°C aluminum sulfate aqueous solution prepared by 333 g of aluminum sulfate 18hydrate and 1332 g of water is added dropwise within 2 h. After the addition is completed, the temperature is increased to 90°C at a rate of 5°C / h, kept warm for 10 minutes, filtered, and the filter cake is washed three times with water 3 times the weight of the filter cake, and dried to constant weight to obtain a polymer additive.
[0085] Example 5 (1) 396 kg of 50% hypophosphorous acid aqueous solution was put into the autoclave, 0.6 MPa nitrogen was used to replace the air in the autoclave for 5 times, ethylene was added until the pressure of the autoclave was 1.0 MPa, and the autoclave was heated to 80°C with stirring and kept warm for 3 hours; 40 g of 10% sodium persulfate aqueous solution was continuously added during the 2-hour heat preservation process; during the heat preservation process, the material in the autoclave was pumped into the liquid inlet of the venturi ejector through the bottom valve of the autoclave by a centrifugal pump and the ethylene gas in the upper layer of the reactor entered from the gas inlet of the venturi ejector, and the gas and liquid phases were fully mixed and circulated into the reactor; new ethylene entered from the gas inlet of the venturi ejector to supplement the ethylene consumed in the reaction to maintain the reactor pressure stable at 1.0 MPa. After the initiator was added, the autoclave was kept warm for 1 hour, cooled and vented to obtain an aqueous solution containing diethylphosphinic acid.
[0086] (2) A sodium hydroxide aqueous solution prepared by 60 g of sodium hydroxide and 1140 g of water was slowly added dropwise to an aluminum sulfate aqueous solution prepared by 333 g of aluminum sulfate 18hydrate and 777 g of water at 15° C. over a period of 1.5 h to obtain an aluminum hydroxide gel solution.
[0087] (3) The aqueous solution of diethylphosphinic acid was diluted to a mass concentration of 25%, 1464 g of which was dripped into the aluminum hydroxide gel solution of step 2) within 2 h, and then the temperature was raised to 115 °C at 20 °C / h, kept warm for 1 h, filtered, and the filter cake was washed three times with water 3 times the weight of the filter cake, and dried to constant weight to obtain a polymer additive.
[0088] Example 6 (1) Take the aqueous solution containing diethylphosphinic acid in step (1) of Example 5.
[0089] (2) At 15° C., a sodium hydroxide aqueous solution prepared by using 60 g of sodium hydroxide and 1140 g of water was slowly added dropwise to an aluminum sulfate aqueous solution prepared by using 333 g of aluminum sulfate 18hydrate and 777 g of water over a period of 1.5 hours to obtain an aluminum hydroxide gel solution.
[0090] (3) 1464 g of a 25% aqueous solution of diethylphosphinic acid in Example 5 was dripped into the aluminum hydroxide gel solution within 2 h, and then the temperature was raised to 115 °C at a rate of 5 °C / h, kept warm for 1 h, filtered, washed three times with 3 times the weight of the filter cake with water, and dried to constant weight to obtain a polymer additive.
[0091] Comparative Example 1 The existing polymer additive 1, BEP-22E, from Zhuhai Jinfa Biomaterials Co., Ltd. was used.
[0092] Comparative Example 2 Existing polymer additive 2, Exolit OP 1230, Clariant, was used.
[0093] Test Case The polymer additives prepared in the above Examples 1 to 6 and Comparative Examples 1 to 2 were subjected to nuclear magnetic phosphorus spectrum testing, and the specific test contents are as follows.
[0094] (1) Instrument: Nuclear magnetic resonance spectrometer (Bruker 400M).
[0095] (2) Reagents: 10 wt% deuterated sulfuric acid aqueous solution.
[0096] (3) Experimental method: Weigh about 0.1 g (accurate to 0.0001 g) of the sample to be tested, add 5 g of 10 wt% deuterated sulfuric acid aqueous solution, and dissolve it by ultrasound; transfer it to a nuclear magnetic resonance tube, and then place the nuclear magnetic resonance tube in a nuclear magnetic resonance analyzer to scan it to obtain a nuclear magnetic resonance spectrum. Integrate the diethyl aluminum phosphinate and ethylbutyl aluminum phosphinate in the nuclear magnetic resonance spectrum to obtain the molar percentage of the two, and after conversion, obtain the mass percentage of the two.
[0097] The test results of the polymer additives are shown in Table 1 below, in terms of mass percentage.
[0098] Table 1
[0099] (2) The polymer additives of the above-mentioned embodiments and comparative examples were tested using the following method.
[0100] Differential Scanning Calorimetry DSC Test: The test was conducted using a NETZSCH DSC 204 F1 instrument, with a test amount of 10 mg of the polymer additive. The polymer additives prepared in each example and the polymer additives in the comparative example were heated from room temperature to a maximum temperature of 300°C at a heating rate of 20°C / min, and then cooled to room temperature at a rate of 20°C / min after being kept at this temperature for 3 minutes, to obtain a cooling curve of the polymer additive. The polymer additives were kept at room temperature for 3 minutes, and then heated again to a maximum temperature of 300°C at a heating rate of 20°C / min to obtain a second heating curve of the polymer additive.
[0101] Select the starting temperature and ending temperature of the exothermic peak on the cooling curve, and calculate the peak area formed by the starting temperature and the ending temperature, which is H1 (crystallization enthalpy), and the peak temperature of this peak is T1; select the starting temperature and the ending temperature of the endothermic peak on the second heating curve, and calculate the peak area, which is H2 (defined as the crystal transformation enthalpy); the peak temperature of this peak is T2. Among them, the double enthalpy ratio ΔH=H2 / H1.
[0102] The peak temperature and peak area are obtained by calibration or calculation using the software provided in NETZSCH DSC 204 F1.
[0103] The above test results are shown in Table 2 below.
[0104] Table 2
[0105] (3) The polymer additives and synergist melamine polyphosphate (MPP) of the above examples and comparative examples were used as flame retardants, mixed with glass fiber and base resin, and extruded to prepare composite materials. The amounts of each component in Examples 7 to 13 and Comparative Examples 3 to 4 are shown in Table 3.
[0106] Corrosion performance test: The corrosion degree of the composite material preparation process of the above-mentioned embodiment and comparative example was tested. The specific operation was as follows: a 20mm×5mm×2mm 304L stainless steel metal block (00Cr19Ni11) was set on the die head of a twin-screw extruder with a screw diameter of 20mm and an aspect ratio of 33:1 (a groove with the same size as the metal block was dug at the bottom of the die head, and the metal block was embedded). The injection temperature was 270℃, and the high-temperature material was in contact with the metal block at the die head. The metal loss (loss weight percentage) after 50kg of material granulation (feed rate of 5kg / h) was tested. The higher the loss, the greater the corrosive value and the worse the corrosion resistance. The measurement results of the embodiment and comparative example are shown in Table 4 below.
[0107] Table 3
[0108] Table 4
[0109] From the data of the embodiment in Table 4, it can be seen that the composite material containing the polymer additive of the present invention has a smaller loss of metal blocks during co-extrusion, indicating that when the double enthalpy ratio ΔH and T1 and T2 of the polymer additive are within a specific range, the polymer additive is less corrosive to the metal block during the flame retardant modification process. The composite material containing the polymer additive of the present invention has a metal loss of ≤0.44 during co-extrusion.
[0110] It can be seen from the examples, comparative examples 3 and 4 that when the double enthalpy ratio ΔH of the polymer additive is within a specific range, the composite material containing the polymer additive is less corrosive to the metal block during co-extrusion, and the polymer additive can significantly reduce the corrosion to the metal parts.
[0111] The foregoing embodiments are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. A polymer additive, characterized in that It comprises diethyl aluminum phosphinate with a structural formula shown in the following formula (I) and ethyl butyl aluminum phosphinate with a structural formula shown in the following formula (II); The polymer additive satisfies the double enthalpy ratio ΔH defined by the following formula (1): 0.92≤ΔH≤1.06; and satisfies 130°C≤T1≤155°C, 165°C≤T2≤185°C; Formula (1) ΔH = H2 / H1; The polymer additive is tested by differential scanning calorimetry (DSC), and the testing method is as follows: in a nitrogen atmosphere, the polymer additive is heated from room temperature to a maximum temperature of 300°C at a heating rate of 20°C / min, and then cooled to room temperature at a rate of 20°C / min after staying at this temperature for 3 minutes, to obtain a cooling curve of the polymer additive; the polymer additive is heated to a maximum temperature of 300°C at a heating rate of 20°C / min again after staying at room temperature for 3 minutes, to obtain a second heating curve of the polymer additive; H1 is the peak area formed by the starting temperature and the ending temperature of the exothermic peak on the cooling curve, and T1 is the peak temperature of the exothermic peak on the cooling curve; H2 is the peak area formed by the starting temperature and the ending temperature of the endothermic peak on the second temperature rising curve, and T2 is the peak temperature of the endothermic peak on the second temperature rising curve.
2. The polymer additive according to claim 1, characterized in that: In terms of weight percentage, the polymer additive comprises: 97.01% to 98.99% of aluminum diethylphosphinate and 1.01% to 2.99% of aluminum ethylbutylphosphinate.
3. The polymer additive according to claim 1, characterized in that: The polymer additive satisfies a double enthalpy ratio ΔH: 0.93≤ΔH≤1.05; the polymer additive satisfies 132°C≤T1≤153°C, 170°C≤T2≤183°C.
4. The method for preparing the polymer additive according to any one of claims 1 to 3, characterized in that: The following steps are involved: a) a water-soluble salt or acid of hypophosphorous acid and an initiator are introduced into a jet loop reaction system to react with an olefin, and 2.00 to 2.05 molecules of olefin are added relative to the P of each water-soluble salt or acid of hypophosphorous acid itself to obtain an intermediate aqueous solution containing diethylphosphinate; b) The intermediate aqueous solution undergoes double decomposition reaction with a water-soluble aluminum salt to obtain a polymer additive.
5. The preparation method according to claim 4, characterized in that: In the step a), the pressure of olefins in the jet loop reaction system is 0.3-3.0 MPa.
6. The preparation method according to claim 4, characterized in that: In the step a), the reaction temperature in the jet loop reaction system is 70-150°C.
7. The preparation method according to claim 4, characterized in that: In the step b), the mass concentration of diethylphosphinate in the intermediate aqueous solution is 20-25%; the mass concentration of the water-soluble aluminum salt in the water-soluble aluminum salt solution is 20-25%.
8. The preparation method according to claim 4, characterized in that: In the step b), the pH of the metathesis reaction is 3.0-3.1; the temperature of the metathesis reaction is 40-45°C.
9. The preparation method according to claim 4, characterized in that: In the step b), the molar ratio of diethylphosphinate in the intermediate aqueous solution to aluminum ions in the water-soluble aluminum salt is 3:1 to 1.
01.
10. The method for preparing the polymer additive according to any one of claims 1 to 3, characterized in that: The method comprises the following preparation steps: a) under nitrogen protection, a water-soluble salt or acid of hypophosphorous acid reacts with an olefin in the presence of an initiator at 90-100° C., keeping the temperature, and adding 2.00 to 2.05 molecules of olefin relative to each P on the water-soluble salt or acid of hypophosphorous acid itself to obtain an intermediate aqueous solution containing diethylphosphinate; b) Under stirring, the intermediate aqueous solution and the water-soluble aluminum salt are mixed and reacted at ≤15°C, and then the temperature is raised to 70-95°C to obtain a polymer additive.
11. The method for preparing the polymer additive according to any one of claims 1 to 3, characterized in that: The method comprises the following preparation steps: a) under nitrogen protection, an aqueous solution of hypophosphorous acid reacts with an olefin in the presence of an initiator at 90-100° C., keeping the temperature, and adding 2.00 to 2.05 molecules of olefin relative to the P of each hypophosphorous acid acid itself to obtain an intermediate aqueous solution containing diethylphosphinic acid; b) preparing an aluminum hydroxide gel solution; c) dropping the intermediate aqueous solution into the aluminum hydroxide gel solution for reaction, raising the temperature to 90-120° C., keeping the temperature for 0.1-5 hours, and post-treating to obtain the polymer additive.
12. Use of the polymer additive according to any one of claims 1 to 3 for reducing corrosion of metal production equipment.
13. Use of the polymer additive according to any one of claims 1 to 3 as a reactive or non-reactive flame retardant for polymers, as a flame retardant for varnishes and foaming coatings, as a flame retardant for wood and other cellulose-containing products, for the preparation of flame-retardant polymer molding materials, for the preparation of flame-retardant polymer moldings or for imparting flame retardancy to polyester and pure and blended cellulose fabrics by impregnation.
14. The use according to claim 13, characterized in that: The polymer additive is used together with a synergist; the synergist is melamine phosphate, melamine pyrophosphate, melamine polyphosphate, melamine and / or melamine cyanurate; it is a nitrogen-containing phosphate of the formula (NH4)yH3-yPO4 or (NH4PO3)z, wherein y is 1 to 3 and z is 1 to 10000; it is aluminum phosphite, aluminum pyrophosphite; it is zinc borate, zinc carbonate, zinc stannate, basic zinc stannate, zinc phosphate, zinc oxide, zinc hydroxide, tin oxide hydrate, basic zinc silicate, magnesium hydroxide, hydrotalcite, magnesium carbonate; it is a salt of ethylphosphonic acid, a salt of butylphosphonic acid, a salt of n-butylphosphonic acid, a salt of sec-butylphosphonic acid and / or a salt of hexylphosphonic acid.
15. The use according to claim 13 or 14, characterized in that: Other additives are used, wherein the other additives are at least one of antioxidants, UV stabilizers, gamma stabilizers, hydrolysis stabilizers, antistatic agents, emulsifiers, nucleating agents, softeners, processing aids, impact modifiers, dyes or pigments.
16. The use according to claim 15, characterized in that: 0.0001 to 99.7999 wt % of the polymer additive, 0.1 to 40 wt % of the synergist and 0.1 to 40 wt % of other additives are used.
17. A flame retardant thermoplastic or thermosetting polymer composite material, characterized in that The invention comprises: 0.5 to 45 wt % of the polymer additive according to any one of claims 1 to 3, 0.5 to 95 wt % of a thermoplastic or thermosetting polymer or a mixture thereof, 0 to 55 wt % of a synergist and 0 to 55 wt % of a filler or a reinforcing material.
18. The flame retardant thermoplastic or thermosetting polymer composite material according to claim 17, characterized in that: The polymer is selected from polyesters, polyamides, thermoplastic elastomers, thermoplastic polyurethanes, thermoplastic polyester elastomers, styrenic polymers, polyketones, polyolefins, polyacrylates and / or polymer blends or other blends comprising polyamides or polyesters.
Citation Information
Patent Citations
Preparation method and application of aluminum monotrifluoropropylphosphinate flame retardant
CN110407869A
Additive for plastics, application thereof, and flame-retardant polymer molding composition composed of the same
CN103937027A
Polymer additive, preparation method and application thereof, and flame-retardant polymer molded composition composed of polymer additive
CN107189098A
Low-corrosivity dialkyl phosphinate composition and application thereof
CN109851852A
Polydialkyl phosphinic acid metal composite salt and / or mixture thereof, and uses thereof
CN111825883A
Cited By
Polymer additive, and preparation method and application thereof
EP4810556A1
Polyamide composite material and application thereof
EP4810557A1
Polymer additive and preparation method, and polymer composition
EP4810558A1